Embroidering Knowledge through Local Wisdom: A Case Study of Interdisciplinary Arts and Science Learning in Elementary Schools: English - Maria Angelina Fransiska Mbari; Benjamin Regi; Yohanes Ehe Lawotan (MIMBAR PGSD Undiksha, 2026)
Interdisciplinary learning in elementary schools often faces challenges due to the separation of subjects, which limits teachers’ ability to connect knowledge across domains meaningfully. This study aims to explore the processes, perceptions, and meanings constructed by teachers in implementing interdisciplinary learning that integrates Arts and Natural and Social Sciences (IPAS) through local wisdom in elementary schools. This study uses a qualitative case study approach. Data were collected through in-depth interviews and observations with six elementary school teachers (three IPAS teachers and three Arts teachers), who were selected using purposive sampling based on their teaching experiences. Thematic analysis was used to analyze the collected data. The results revealed three interrelated themes that formed a transformative narrative. First, the existence of “walls of separation” from a fragmented curriculum that created pedagogical challenges. Second, the emergence of a “longing for bridges of collaboration” from teachers who desired more integrated and meaningful teaching practices. Finally, local wisdom was identified as an authentic and effective “bridge of knowledge,” enabling teachers to “weave” scientific concepts and artistic expressions into a culturally responsive pedagogy. This approach not only connects disciplines but also validates students' cultural identities by using their environment as a primary learning resource. The implications of this research highlight the potential of local wisdom as a foundation for curriculum innovation and teacher professional development to promote interdisciplinary, culturally grounded learning in schools.